Lack of Fractalkine Receptor on Macrophages Impairs Spontaneous Recovery of Ribbon Synapses After Moderate Noise Trauma in C57BL/6 Mice - Kaur, Tejbeer; Clayman, Anna C.; Nash, Andrew J.; Schrader, Angela D.; Warchol, Mark E.; Ohlemiller, Kevin K. (Frontiers in Neuroscience, 2019)
Noise trauma causes loss of synaptic connections between cochlear inner hair cells (IHCs) and the spiral ganglion neurons (SGNs). Such synaptic loss can trigger slow and progressive degeneration of SGNs. Macrophage fractalkine signaling is critical for neuron survival in the injured cochlea, but its role in cochlear synaptopathy is unknown. Fractalkine, a chemokine, is constitutively expressed by SGNs and signals via its receptor CX3CR1 that is expressed on macrophages. The present study characterized the immune response and examined the function of fractalkine signaling in degeneration and repair of cochlear synapses following noise trauma. Adult mice wild type, heterozygous and knockout for CX3CR1 on a C57BL/6 background were exposed for 2 hours to an octave band noise at 90 dB SPL. Noise exposure caused temporary shifts in hearing thresholds without any evident loss of hair cells in CX3CR1 heterozygous mice that have intact fractalkine signaling. Enhanced macrophage migration towards the inner hair cell-synaptic region was observed immediately after exposure in all genotypes. Synaptic immunolabeling revealed a rapid loss of synapses throughout the basal turn of the cochlea of all genotypes. The damaged synapses spontaneously recovered in mice with intact CX3CR1. However, CX3CR1 knockout (KO) animals displayed enhanced synaptic degeneration that correlated with attenuated suprathreshold neural responses at higher frequencies. Exposed CX3CR1 KO mice also exhibited increased loss of IHCs and SGN cell bodies compared to exposed heterozygous mice. These results indicate that macrophages can promote repair of damaged synapses after moderate noise trauma and that repair requires fractalkine signaling.